Length weight relationships of two small indigenous cyprinid fishes, Osteobrama cotio (Hamilton, 1822) and Salmophasia phulo (Hamilton, 1822) from Panchet Reservoir, Damodar River (tributary of River Ganga), India. (8th March 2017) - Sandhya, K. M.; Sarkar, U. K.; Karnatak, G.; Lianthuamluaia, L.; Kumar, V.; Kumari, S.; Panda, D.; Mishal, P.; Ali, Y.
Summary: Length–weight relationships were determined for two small indigenous cyprinid fishes: Osteobrama cotio (Hamilton, 1822) and Salmophasia phulo (Hamilton, 1822) collected from Panchet reservoir, Damodar River, India. About 143 specimens of Osteobrama cotio (5.2–10.4 cm TL) and 113 specimens of Salmophasia phulo (2.9–8.2 cm TL) were collected from November 2014 to June 2016 using gillnets of mesh size ranging from 25 to 120 mm (STR) and dragnets of mesh size 10–20 mm (STR). No previous information on LWRs for these two species from an Indian reservoir was available in the literature.